Changing Perspectives of Local Therapists Eight Years after the Implementation of an Occupational Therapy Service in a Unique Himalayan Cross-Cultural Setting - Gaby Scheidegger; Zhang Ting Ting; Caroline Bastiaenen; Michael Nagler (Occupational Therapy International)
Background. Whether concepts and principles of Occupational Therapy (OT) can successfully be applied to non-Western and cross-cultural settings is being intensively discussed. Aims/Objectives. We explored the changing perspectives of local occupational therapists (OTs) eight years after the implementation of an OT service in a Himalayan cross-cultural setting in terms of (1) treatment applied, (2) professional identity, and (3) cross-cultural interactions. Material and Methods. A qualitative study design was chosen, and semistructured interviews were conducted in all employed practitioners (a) during implementation and (b) eight years later n=7. Questions were carefully formulated in order to narrow down the intended issues but respecting crosscultural differences. The framework method was implemented for data analysis. Findings. Long-term empowering local OTs resulted in the successful development of a sustainable OT department in a unique Himalayan cross-cultural setting. Practitioners became aware of their therapeutic potentials, a clear sense of professional identity was developed, and it was recognised that sensitive cross-cultural practice is only achieved by an ongoing and intentional cultural learning process. Conclusions and Significance. Our findings suggest that OT can be applied to non-Western cross-cultural settings.